ANALISIS IMPLEMENTASI SISTEM PENGENDALIAN INTERN PENGELOLAAN PIUTANG DENGAN MENGGUNAKAN PENDEKATAN TECHOLOGY ACCEPTANCE MODEL (TAM) - Miftahurrohman; Isnaini, Leny; Kusumajaya, Robby Andika (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
Accounts receivable management for financial services organizations has a very strategic position, to minimize the risks of accounts receivable that can disrupt business operations. Implementation of an accounts receivable management information system is an effort made by organizations to minimize the impacts of accounts receivable losses. However, the success rate of system implementation is still relatively low and still expensive, so it is necessary to conduct an analysis of the implementation of an information system to determine the factors that influence user behavior in using the information system. By using the technology accepted model (TAM) approach to identify factors that influence users in using the information system. The results of the study explain that the perception of user convenience does not affect the intention of information system users, attitudes towards using information system technology and actual use of technology. While the perception of usefulness has a significant influence on the perception of user convenience and the attitude of information system users. Other results of this study indicate that the attitude of using the information system affects the intention of information system users, and the intention of information system users affects the actual use of technology.